1978
DOI: 10.1136/jcp.31.10.939
|View full text |Cite
|
Sign up to set email alerts
|

Astrovirus-associated gastroenteritis in children.

Abstract: SUMMARY In a small astrovirus-associated outbreak of gastroenteritis in a ward of a local children's hospital two out of five children with symptoms excreted astrovirus particles. No astrovirus particles were found in faeces from the remaining asymptomatic child, and no other viral or bacterial pathogens were found in any of the children. Virus excretion persisted for only a few days. Rising antibody titres to the astrovirus particles were demonstrated in one child, and IgM was also demonstrated in this patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 12 publications
2
40
0
Order By: Relevance
“…Children, from infancy to 5 to 7 years of age, are most likely to develop symptomatic disease with astroviruses (7,204,210), although exposed adults can also develop mild disease, but with less frequency (204,210,278). In one study (210), older children were also found to be less likely to develop disease than younger children.…”
Section: Astrovirusesmentioning
confidence: 95%
See 3 more Smart Citations
“…Children, from infancy to 5 to 7 years of age, are most likely to develop symptomatic disease with astroviruses (7,204,210), although exposed adults can also develop mild disease, but with less frequency (204,210,278). In one study (210), older children were also found to be less likely to develop disease than younger children.…”
Section: Astrovirusesmentioning
confidence: 95%
“…However, in another study, some children had vomiting only, while the remainder suffered from both vomiting and diarrhea (7). In a third study, the rates of symptoms were as follows: vomiting, 74%; diarrhea, 30%; abdominal pain, 49%; and fever, 30% (204).…”
Section: Astrovirusesmentioning
confidence: 99%
See 2 more Smart Citations
“…Caliciviruses are 30 nm in diameter, having a feathery edge and a six-pointed star with a central hollow (Madeley and Cosgrove, 1976;McSwiggan, Cubitt and Moore, 1978). Astroviruses, having a diameter of 28 nm, are characterised by a smooth edge and a five-or six-pointed star with no central hollow (Madeley and Cosgrove, 1975;Ashley, Caul and Paver, 1978).…”
Section: Introductionmentioning
confidence: 99%